Crossover stars in the Hindi film industry : globalizing Pakistani identity - Khdair, Dina (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book explores the cultural politics of Pakistani crossover stardom in the Hindi film industry as a process of both assimilation and 'Otherness'. Analysing the career profiles of three crossover performers-Ali Zafar, Fawad Khan, and Mahira Khan-as a relevant case study, it unites critical globalization studies with soft power theory in exploring the potential of popular culture in conflict resolution. It studies the representation and reception of these celebrities, while discussing themes such as the meaning of being a Pakistani star in India, and the consequent identity politics that come into play. As the first comprehensive study of Pakistani crossover stardom, it captures intersections between political economy, cultural representation and nationalist discourse, at the same time reflecting on larger questions of identity and belonging in an age of globalization. Crossover Stars in the Hindi Film Industry will be indispensable to researchers of film studies, media and cultural studies, popular culture and performance, peace and area studies, and South Asian studies. It will also be of interest to enthusiasts of Indian cinematic history"--
A historical legacy -- Globalization, new political economies, and cultural change -- Aspirational affects and boundary crossing : Ali Zafar, the Pakistani 'Prince of Pop' -- A crossover romance : female fandom and Fawad Khan, Pakistan's 'reel' gentleman -- I am not your feminist : Mahira Khan and the re-scripting of Pakistani womanhood, Islam and globalization -- A fragile union : moving forward, facing backward.
OCLC-licensed vendor bibliographic record.
Keywords: Zafar, Ali, -- 1980-; Khan, Fawad, -- 1981-; Khan, Mahira, -- 1982-; Motion picture industry -- Political aspects -- India; National characteristics, Pakistani; Motion picture actors and actresses -- India; Motion picture actors and actresses -- Pakistan; Pakistanis -- India -- Social conditions; India -- Relations -- Pakistan; Pakistan -- Relations -- India; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Sociology / General